Acquired pellicle engineering: a fascinating approach to prevent demineralization - Carolina Ruis FERRARI; Matthias HANNIG; Marília Afonso Rabelo BUZALAF (Journal of Applied Oral Science)
Abstract The acquired enamel pellicle (AEP) consists of an organic, acellular, and bacteria-free film, formed in vivo as a result of biomolecules adsorption onto the tooth surface. It is composed of proteins, glycoproteins, lipids, phospholipids, and other macromolecules, such as carbohydrates. The AEP formation process is complex and can be divided into three stages: initiation, development, and maturation. The pellicle has two main layers: the globular and basal layers. The basal layer offers the most protection against demineralization, as the subsequent globular layer is weaker and less tenacious. The formation of the AEP can be influenced by various factors, such as the physicochemical properties of the teeth, location in the oral cavity, pathologies, and even the oral microbiota. With the advancement of “omics” techniques, it has been possible to observe the presence of acid-resistant proteins in the AEP, which allowed the development of the “acquired pellicle engineering” strategy. This strategy involves enriching and modifying the basal layer with acid-resistant proteins. Among these proteins, hemoglobin, statherin-derived peptide, and a protein derived from sugarcane stand out. The objective of this literature review is to provide a comprehensive overview of the AEP, detailing its composition, formation process, and protective functions. Additionally, the review aims to explore recent advances in the field of “acquired pellicle engineering,” highlighting the acid-resistant proteins of the AEP and their potential applications in dentistry. Finally, the review intends to highlight the clinical implications of these findings and how they may contribute to the development of new strategies for the prevention and treatment of dental pathologies according to published studies.